Comparison of Neutrophil-to-Lymphocyte Ratio (NLR) in Gram-Positive and Gram-Negative Bacteremia from Blood Specimens - Surahmat, Erik; Suhartini, Anita (Jurnal Analis Medika Biosains (JAMBS), 2025)
Bacteremia remains a significant cause of morbidity and mortality worldwide, with both Gram-positive and Gram-negative bacteria contributing to the disease burden. The neutrophil-to-lymphocyte ratio (NLR) has emerged as a simple, cost-effective biomarker for evaluating inflammation and infection severity. This study aimed to compare the NLR values between patients with Gram-positive and Gram-negative bacteremia confirmed by blood culture. An analytical observational cross-sectional study was conducted at Bayu Asih Purwakarta Hospital from January to July 2025. Data from patients with positive blood cultures and complete hematological profiles were included and analyzed using the Mann-Whitney U test. A total of 84 cases were studied, consisting of 42 Gram-positive and 42 Gram-negative bacteremia. The results showed a statistically significant difference in NLR values between the two groups (p = 0.038. These findings support the utility of NLR as a useful biomarker in differentiating types of bacterial infections in bacteremia cases. In conclusion, NLR may aid in early diagnosis and clinical decision-making for bacteremia management.